Here's the question you clicked on:
henaoalexandra
x^2-x=6
What do you wanna do with it?
if you want to solve the easiest way you could do so so is by Factoring
EXAMPLE FACTORING X^ 2 + X = 12 X^2 + X - 12 = 0 ( X + 4 ) ( X - 3 ) = 0 X= -4 , 3
x^2-x=6 Here you start by taking 6 away from both sides of the equation and you have: x^2-x-6=6-6 x^2-x-6=0 Here you can easy factor (x-3)(x+2)=0 first divide by x-3 and you get x+2=0 Take away 2 from both sides x+2-2=0-2=> x=-2 Now you go back to (x-3)(x+2)=0 and divide by x+2 and you get x-3=0 =>x=3 So the initial equation x^2-x=6 has two roots; they are -2 and 3